Vivere il mondo, vivere nel mondo. Agostino in Heidegger - Esposito, Costantino (Bollettino Filosofico, 2020)
One of the themes of Heidegger’s works where Augustine’s presence can be caught is the problem of the World, or more precisely the world as an ontological dimension of human being. This contribution aims at reading again some extracts from Augustine’s writings (especially The Confessions) through Heidegger’s eyes, in order to point out the direct or indirect influence exerted by the Augustinian descriptions of men as mundi habitatores (those who inhabit the world) and dilectores mundi (those who love the world) upon Heidegger’s notion of Dasein as Being-in-the-World. The works that this essay will deal with, about this theme, are Heidegger’s first Freiburg courses of Twenties, the Natorp-Bericht and, of course, Sein und Zeit and Vom Wesen des Grundes. Nevertheless, the second part of this essay tries an opposite intervention, that is to read some moments of Heidegger’s existential analytics through Augustine’s eyes, by a direct analogy between the dynamics of temtatio (the trial which life is always submitted to), the defluxus in multa (the dispersion of I parting from You until vanishing into the world) and the facticity of existence, the thrownness and the dread of Dasein. If, on the one hand, it is true that in some times of his itinerary Heidegger had found himself, and even mirrored, in Augustine, on the other hand it is true that afterwards he had to get away from him, so as not to get to the point from which Augustine’s thought found all its origin and rootedness. Keywords: Augustine, Being-in-the-World, Facticity, Heidegger, Thrownness